ANALISIS DETERMINASI FAKTOR PENYUSUNAN LAPORAN KEUANGAN UMKM BERBASIS SAK EMKM - Pratiwi, Ani; Widayati, Neneng; Fauzi, Fauzi (E-Jurnal Akuntansi TSM, 2025)
The preparation of financial statements based on SAK EMKM remains a challenge for MSMEs, particularly due to limited accounting comprehension, varying business scales, and differing levels of digital technology adoption. This study aims to examine the influence of QRIS implementation, business size, and accounting comprehension on the preparation of financial statements in accordance with SAK EMKM among MSMEs. A quantitative approach was employed by distributing questionnaires to 100 MSME respondents, with data analysed using the SEM-PLS method. The findings indicate that all three independent variables significantly affect the application of SAK EMKM. QRIS contributes to improved transaction recording and accountability, business size influences the extent of compliance with reporting standards, while accounting comprehension emerges as the dominant factor in enhancing the quality of MSMEs’ financial statements. These results underline the importance of integrating digital financial technologies with accounting literacy in encouraging MSMEs to prepare reports in line with standards. The study suggests that government bodies, MSME associations, and educational institutions should strengthen practical accounting literacy programmes alongside digital mentoring to promote broader implementation of SAK EMKM. Future research is recommended to expand the geographical scope, apply a longitudinal approach, and include external variables such as regulatory support and business environment.